CFD FLOW ANALYSIS OF THE CANTILEVER MICRO-TURBINE - Tomáš Syka; Andreas P. Weiß (Acta Polytechnica CTU Proceedings)
The article deals with a description of results from research and development of the cantilever micro-turbine designed for the ORC power plants. The experimental turbine stage and used numerical models are briefly described. In the first part the comparison of measured and CFD results is presented. The second part deals with an investigation of the outlet geometry influence on the turbine working parameters. The results are relevant for next studies in the research and development process.